Adam dan Kristus: Studi Komparasi Antara Penghukuman Dan Pembenaran Allah Berdasarkan Roma 5:18-19 - Warseto Freddy Sihombing; Seri Antonius (Sekolah Tinggi Teologi Berita Hidup, 2022)
AbstractSalvation in Jesus Christ is only obtained by sinners through faith. Without faith in Jesus Christ, no one will be saved. God only justifies those who believe in Jesus Christ, so they will not receive God's wrath. By inductive method, this article explores the truth of apostle Paul's statement in Romans 5:18-19; that disobedience of first Adam made all men being sinful and cursed. On the other hand, the Jesus Christ’s obedience as the second / last Adam has made sinful men being right before God and have hope for eternal life. Paul gives a comparison between Adam and Christ — between the first Adam and the last Adam. The first Adam has caused men (his descendants) commite to sin, but the second/last Adam has finally provided a way out of God’s punishment and wrath. This is a great grace of God.Keywords: first adam; second adam; obedience; disobedience; justification; comparisonAbstrakKeselamatan di dalam Yesus Kristus hanya diperoleh orang berdosa melalui iman. Tanpa iman kepada Yesus Kristus, seorang pun tidak akan beroleh keselamatan. Allah hanya membenarkan mereka yang beriman kepada Yesus Kristus, dengan demikian mereka tidak akan mengalami murka Allah. Dengan metode induktif, artikel ini menggali kebenaran dari pernyataan rasul Paulus dalam Roma 5:18-19; bahwa ketidataaktaatan Adam pertama telah menjadikan semua manusia berdosa dan terkutuk. Di pihak lain, ketaatan Yesus Kristus sebagai Adam kedua/terakhir telah menjadikan manusia yang telah berdosa tersebut benar di hadapan Allah dan memiliki pengharapan untuk memperoleh hidup kekal. Paulus memberikan sebuah komparasi antara Adam dan Kristus—antara Adam pertama dan Adam terakhir. Adam pertama telah mengakibatkan manusia (keturunannya) berdosa, tetapi Adam kedua/terkahir telah memberikan jalan keluar dari penghukuman dan murka Allah. Ini merupakan kasih karunia Allah yang besar.Kata-kata kunci: adam pertama, adam kedua, ketaatan, ketidaktaatan, pembenaran, komparasi